AROUND THE FALL OF SUHARTO: A CRITICAL ANALYSIS OF RICHARD MANN’S PLOT AND SCHEMES THAT BROUGHT DOWN SOEHARTO (PSBDS) - Sugeng Purwanto (Dinamika Bahasa dan Budaya, 2009)
The real cause of Soeharto’s fall from the Indonesian presidency remains a mystery. Richard Mann (1998) launched three significant rhetorical questions, i.e. (1) Was President Soeharto toppled by student demonstrators and people’s power? (2) Was he brought down by the withdrawal of support from the United States? (3) Or, was his sudden fall brought about by all of the two plus large doses of Oriental plotting and scheming? This paper attempts to analyze Richard Mann’s PSBDS in terms of its macrostructure in order to find out the real cause of Soeharto’s fall. The analysis is substantiated by different resources as linguistic evidences, to justify the validity of the findings. The study critical reading is the key to successful comprehension of a text, of which crosschecking with other resources is one. Key words: rhetorical questions, people’s power, oriental plotting and scheming, macrostructure, critical reading